Assistive technologies as part of a digital ecosystem - Calder, David (Edizioni ETS, 2008)
There is a rapidly growing requirement for a new approach to the design of computer-based assistivesystems for the disabled. Within a disparate classification of user requirements, many systemsmanufacturers have catered for particular disabilities in relative isolation and not necessarily within thewider context of other modalities and areas of disability. The Digital Ecosystems for AssistiveTechnologies (DESAT) approach would assist therapists, educationalists, manufacturers andacademic researchers, by offering a coordinated digital ecosystem from which both the ecologicallyembedded end user and support teams from diverse disciplines could benefit.